Mechanisms of Elevated Sulfate Concentrations in High Geotemperature Coal Mining Areas - Li, Yuanmeng (International Journal of Natural Resources and Environmental Studies, 2025)
Sulfate (SO₄²⁻) contamination in groundwater within mining areas has garnered widespread global attention, while prolonged coal mining activities have further complicated geological conditions and hydrogeochemical environments. This study investigates the sources and evolution of SO₄²⁻ in the Pingdingshan coal mining area based on multi-year hydrochemical data. Key findings are as follows:Ion correlation analysis demonstrates that cation exchange between Na⁺ and Ca²⁺/Mg²⁺ dominates hydrogeochemical processes in the groundwater; Spatiotemporal sulfate variations, analyzed through hydrochemical data and statistical methods, reveal that sulfate concentrations in the sandstone aquifer exhibit the most significant fluctuations under mining impacts, whereas phreatic and limestone groundwater sulfate concentrations oscillate within a range of 200 mg/L; Comparative analysis between the Pingdingshan (high geotemperature mining area) and Jiaozuo (ambient-temperature mining area) coal regions indicates that elevated geotemperature, water circulation, and water-rock interactions enhance mineral dissolution and sulfide oxidation, leading to anomalously high sulfate concentrations in groundwater; This study elucidates the migration and evolution mechanisms of SO₄²⁻ in the study area, providing critical insights for mitigating sulfate contamination in groundwater systems of high geotemperature coal mining regions in North China.